Dependence of acoustic properties on hydrate-bearing sediments with heterogeneous distribution. (1st October 2020) - Ren, Liang-Liang; Qi, Ya-Hui; Chen, Jun-Li; Sun, Yi-Fei; Sun, Chang-Yu; Wang, Xiao-Hui; Chen, Guang-Jin; Yuan, Qing; Pang, Wei-Xin; Li, Qing-Ping
Highlights: A method to prepare hydrate deposit with heterogeneous distribution was proposed. The influence of water migration on P-wave velocity and amplitude was examined. Hydrate formation process was divided into unconsolidated and consolidated stages. P-wave velocity with homogeneous distribution is faster than heterogeneous one. Layered distribution hydrate provided direct evidence about heterogeneous degree. Abstract: The relationship between the hydrate-bearing sediments with physical properties such as wave velocity is of importance for the exploration and exploitation of natural gas hydrate. The distribution modes of naturally occurring gas hydrates in sediments are diverse and have significant influence on physical properties of rocks. However, hydrates in homogeneous distribution are in general investigated in laboratory currently. In this work, to simulate the diverse distribution modes of naturally occurring gas hydrates, a novel method to prepare the hydrate-bearing sediments with heterogeneous distribution including layered distribution was proposed by controlling the temperature, water migration, and water saturation distribution. Velocity and amplitude of P-wave are investigated to evaluate the physical properties of hydrate-bearing sediments with homogeneous or heterogeneous distribution. The results showed that the hydrate formation process apparently consists of unconsolidated and consolidated steps according to the amplitude curve. The amplitude of P-wave in the unconsolidated stage increases slowly, while it increases suddenly and rapidly in the consolidated stage. The P-wave velocity of the hydrate deposits with homogeneous distribution is faster than that with heterogeneous distribution when under a same hydrate saturation. This is also verified from the experiments performed on hydrate-bearing sediments with layered distribution, which provided direct evidence and quantification about heterogeneous degree of hydrate distribution in sediment. This difference of the P-wave velocity between heterogeneous and homogeneous hydrate-bearing sediments would provide a guidance in the future development of natural gas hydrate.